Oxidative dehydrogenation of Propane over vanadium catalysts - Eghreibeel, Hanan; M. Korbag, Issa; Alamaryb, Halima; Mahmoud, Sabri; Hammoudeh, Ayman (Libyan Journal of Science &Technology, 2022)
Oxidative dehydrogenation of Propane over vanadium catalysts